Orchestrating talent development: youth players' developmental experiences in Scandinavian team sports - Thue Bjørndal, C.; Ronglan, L. T. (Sports Coaching Review, 2017)
The aim of this study was to investigate athletes` contemporary experiences of their pursuits toward the adult elite level within a Scandinavian team sport setting. The athletes in this study were involved in multiple teams that were led by different coaches. 12 youth handball players, aged 16-17 years, with national team experience were interviewed in-depth. The interviews were transcribed verbatim and an inductive analysis was undertaken. The findings revealed five main themes central to the players` pursuits: (a) time pressure and prioritising; (b) complimentary influences; (c) conflicting goals and demands; (d) balancing load and recovery; and (e) coordination challenges. The conceptual notion of coach orchestration is shown to be potentially relevant to understanding the role of coaches involved in talent development. In this paper, the concept of coach orchestration is expanded to encompass what coaches must consider to facilitate individual development within and across different team settings.